Enemy or friend: the personal and the factual patient-physician relationship - Keller, Frieder; Ludwig, Ulla; Huber-Lang, Markus (Frontiers in Medicine, 2023)
Physicians are expected to place the patient’s interests above their own. Such prioritization has worldwide consent. It constitutes the difference between medicine and other professions. The present conceptual opinion paper summarizes the authors’ clinical experience with patient care and student teaching during the last 45 years. The authors comment on their own conception by referring to present debates and prominent statements from the past. Fundamental changes in medicine have taken place over the last five decades. New diseases have emerged while diagnostic and therapeutic options for patients have grown steadily – along with healthcare costs. At the same time, economic and legal constraints for physicians have increased, as has moral pressure. The interaction of physicians with patients has gradually shifted from a personal to a factual relationship. In the factual, more formal relationship, the patient and physician represent equal partners of a legal contract, which jeopardizes the prioritization of the patient’s interests. The formal relationship implies defensiveness. By contrast, in the personal relationship, the physician adopts an existentialist commitment while simultaneously enabling and respecting the patient’s autonomous decision-making. The authors argue for the personal relationship. However, the patient and physician are no friends. Consequently, the physician in effect competes with the patient from a knowledge-based but opposite position. Both need to make efforts to consent and maintain the relationship even when they dissent. This implies that the physician does not simply comply with the patient’s wishes.